1997
DOI: 10.1073/pnas.94.12.6397
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin:In vitrosynthesis,in vivotissue expression, and subcellular localization identifies a large membrane-associated protein

Abstract: The primary structure of polycystin predicts a large integral membrane protein with multiple cell recognition motifs, but its function remains unknown. Insight into polycystin's normal function and its role in the development of autosomal dominant polycystic kidney disease (PKD1) requires the assembly of an extensive collection of molecular reagents to examine its expression and create model systems for functional studies. Development of these crucial reagents has been complicated due to the presence of transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
4
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 31 publications
11
154
4
4
Order By: Relevance
“…Apart from the study of Griffin et al 27 that observed no polycystin-1 expression in the adult, this later distal expression pattern persisting into adult life has been observed in several other studies. 20,28,29 The expression of the ADPKD proteins appears only weakly in the earliest nephrogenic precursors, and is consistent with data from the Pkd1 Ϫ/Ϫ knockout mouse, 30 where formation of the nephron appears to occur normally; the role of these proteins is thus probably in tubular elongation and the maintenance of tubular architecture rather than in epithelial induction.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Apart from the study of Griffin et al 27 that observed no polycystin-1 expression in the adult, this later distal expression pattern persisting into adult life has been observed in several other studies. 20,28,29 The expression of the ADPKD proteins appears only weakly in the earliest nephrogenic precursors, and is consistent with data from the Pkd1 Ϫ/Ϫ knockout mouse, 30 where formation of the nephron appears to occur normally; the role of these proteins is thus probably in tubular elongation and the maintenance of tubular architecture rather than in epithelial induction.…”
Section: Discussionsupporting
confidence: 71%
“…We previously described the highest levels of adult PKD1 gene expression in the brain. 13 Unlike others, 29 we did not observe polycystin-1 (or polycystin-2) expression by astrocytes, but rather by neuronal cell bodies throughout the developing brain. However, no neural phenotype has been reported for ADPKD, indicating that the presence of one mutant allele does not disrupt neural development.…”
Section: Discussionmentioning
confidence: 69%
“…In ADPKD patients, expression levels of the PKD1/PKD2 mutated allele can be strongly or mildly reduced. Paradoxically, PKD1/PKD2 and PC1/PC2 are found overexpressed in human ADPKD kidneys (3,(62)(63)(64)(65)(66)(67). The severity of the ADPKD cystogenic mechanism(s) is likely to depend on modulation of the remaining non-mutant copy of PKD1/PKD2 potentially through de novo mutations, a stochastic event, altered functional role of polycystins and/or epigenetic inheritance that are actively under study.…”
Section: Upregulation Of C-myc In Human Adpkdmentioning
confidence: 99%
“…On the other hand, there is also evidence that the majority of cysts show strong immunoreactivity with antibodies directed against both polycystins. [13][14][15][16] The aim of this study was to search for LOH in microsatellites linked to PKD1 and PKD2 genes and the chromosome 3 marker which is frequently deleted in some tumors 7 in epithelial cystic cells from ADPKD patients. We have analysed 211 renal and hepatic cysts from seven different patients for LOH, and have detected a 13.3% LOH for PKD1.…”
Section: Introductionmentioning
confidence: 99%